Distribusi Dan Kelimpahan Meiofauna Di Perairan Kuala Jeumpa Kecamatan Jeumpa, Kabupaten Bireuen - Fitria Hanum; M. Ali Sarong; Chitra Octavina (Jurnal Ilmiah Mahasiswa Kelautan Perikanan Unsyiah, 2017)
ABSTRACTThis study was conducted to determine the abundance and distribution of meiofauna in the Kuala Jeumpa waters, Jeumpa subdistrict, Bireuen regency. Sampling was conducted in April until May 2016. Purposive sampling method was used to determine the 3 stations of data collection, which includes downstream, upstream and estuary area, and then the data was analyzed in the laboratory. The results obtained from the abundance of meiofauna ranging from 222 ind/m2 - 3963 ind/m2 was made up of an abundance of Acarina sp. 222 ind/m2, abundance of Annulonemertes sp. 593 ind/m2, abundance of Cumacea sp. 481 ind/m2, abundance of Cyatholaimus sp. 3963 ind/m2, abundance of Eggerelloides scabrous 630 ind/m2, abundance of Kalipthorincia sp. 1037 ind/m2, abundance of Patagonacyther senescens 556 ind/m2, abundance of Syllides sp. 1593 ind/m2 and an abundance of Decapoda 407 ind/m2. Meiofauna with the highest abundance in the Kuala Jeumpa waters is Cyatholaimus sp. and the lowest was Acarina sp. Distribution Acarina sp. to Decapoda is clustered. The conclusion that the abundance of meiofauna ranging between 222 ind/m2 - 3963 ind/m2. The types of sediment are smooth sand and medium sand.Keywords: Abundance, distribution, meiofauna, Cyathulaimus sp., Acarina sp., Kuala Jeumpa waters ABSTRAKPenelitian ini dilakukan untuk mengetahui kelimpahan dan distribusi meiofauna di Perairan Kuala Jeumpa Kecamatan Jeumpa, Kabupaten Bireuen. Pengambilan sampel dilakukan pada bulan April – Mei 2016. Metode purpossive sampling digunakan untuk menentukan 3 stasiun pengambilan data, yang meliputi kawasan hilir, hulu dan muara sungai, kemudian sampel yang ditemukan dianalisis di laboratorium. Hasil yang didapat dari kelimpahan meiofauna berkisar 222 ind/m2 – 3963 ind/m2 adalah terdiri dari kelimpahan Acarina sp. 222 ind/m2, kelimpahan Annulonemertes sp. 593 ind/m2, kelimpahan Cumacea sp. 481 ind/m2, kelimpahan Cyatholaimus sp. 3963 ind/m2, kelimpahan Eggerelloides scabrous 630 ind/m2, kelimpahan Kalipthorincia sp. 1037 ind/m2, kelimpahan Patagonacyther senescens 556 ind/m2, kelimpahan Syllides sp. 1593 ind/m2 dan kelimpahan Decapoda 407 ind/m2. Kelimpahan meiofauna tertinggi di perairan Kuala Jeumpa adalah Cyatholaimus sp. dan terendah adalah  Acarina sp. Pola distribusi Meiofauna di perairan Kuala Jeumpa adalah mengelompok. Jenis sedimen di perairan Kuala Jeumpa adalah pasir sedang dan pasir halus.Kata kunci: Kelimpahan, distribusi, meiofauna, Cyatholaimus sp., Acarina sp., Kuala Jeumpa.